Fair Value and Historical Cost Dilemma: Modern Accounting Dynamics in Financial Statement Quality - Kenley Maccauley Riyono; Rafael Savio Easter; Kelvin Danendra; Wirawan Endro Dwi Radianto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The use of fair value and historical cost is still debated in modern accounting regarding its application and effect on the quality of financial statements. Moreover, there is a conflict of interest between managers and stakeholders related to the need for asset valuation based on these methods. Therefore, a solution is needed to balance between relevance and reliability to meet the needs. This study aims to determine the effect of applying fair value and historical cost on financial statement information during economic volatility. The sample used is representative of companies in the financial, property, and energy sectors that were affected by the application of valuation methods during the financial crisis in 2008 and the COVID-19 pandemic in 2020. The research was conducted using the content analysis method and literature review to find out more about the financial statements. The results show that fair value exacerbates the company's financial decline during the volatility of the financial crisis, but describes the current condition of the company so which is relevant, but not reliable due to the subjectivity of valuation. Whereas historical cost does not result in changes so it is not relevant, but more reliable due to objectivity and verifiability. With this, the research contributes to provide input in the application of both methods with a hybrid approach in financial statements.